2005
DOI: 10.1098/rspb.2005.3327
|View full text |Cite
|
Sign up to set email alerts
|

Visual search for a target changing in synchrony with an auditory signal

Abstract: We examined whether the detection of audio-visual temporal synchrony is determined by a pre-attentive parallel process, or by an attentive serial process using a visual search paradigm. We found that detection of a visual target that changed in synchrony with an auditory stimulus was gradually impaired as the number of unsynchronized visual distractors increased (experiment 1), whereas synchrony discrimination of an attended target in a pre-cued location was unaffected by the presence of distractors (experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 49 publications
(77 reference statements)
7
72
5
Order By: Relevance
“…This could help reduce effective set size, and thus perceptual load, allowing audio-visual integration to be more effective. This explanation is indirectly supported by previous findings indicating that cross-modal integration under highperceptual-load conditions is mediated by a serial, attentive process [38,39,52], and therefore should be more effective in conditions where there are fewer possible auditory-visual associations. Audio-visual coincidence selection can be enabled in a variety of ways, such as using sparse visual displays (as in many multi-sensory enhancement experiments), or by the saliency and temporal informativeness of the accessory acoustic cue [36].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This could help reduce effective set size, and thus perceptual load, allowing audio-visual integration to be more effective. This explanation is indirectly supported by previous findings indicating that cross-modal integration under highperceptual-load conditions is mediated by a serial, attentive process [38,39,52], and therefore should be more effective in conditions where there are fewer possible auditory-visual associations. Audio-visual coincidence selection can be enabled in a variety of ways, such as using sparse visual displays (as in many multi-sensory enhancement experiments), or by the saliency and temporal informativeness of the accessory acoustic cue [36].…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, paradigms where perceptual load is high (i.e. when the matching between sound and visual events must be extracted from complex, dynamically changing events) have typically failed to demonstrate cross-modal enhancement in search tasks [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…This may be critical to the low-level interactions between the two modalities reported by these studies. Many studies have reported that attention is a prerequisite for observing multisensory integration (Alsius, Navarra, Campbell, & Soto-Faraco, 2005;Alsius, Navarra, & Soto-Faraco, 2007;Fujisaki, Koene, Arnold, Johnston, & Nishida, 2006;Talsma, Doty, & Woldorff, 2007), although others report findings to the contrary ( Van der Burg et al, 2008a;and see Talsma, Senkowski, Soto-Faraco, & Woldorff, 2010, for a recent review regarding the role of attention in multisensory integration).…”
Section: Discussionmentioning
confidence: 99%
“…The mean 4 Hz stimulation rate (range of 2-10) used here, together with the constraints (protective window, see Fig. 1 B) implemented to avoid any accidental synchronies in the noncorresponding condition, should optimize detection of audiovisual correspondence versus noncorrespondence (Fujisaki et al, 2006) but make these bimodal conditions otherwise identical in terms of the temporal patterns presented overall to each modality. All sequences were created individually for each subject using Matlab 6.5 (MathWorks, Natick, MA).…”
Section: Methodsmentioning
confidence: 99%